Development of high-performance bismuth sulfide nanobelts humidity sensor and effect of humid environment on its transport properties - Muhammad Faheem Afsar (2020)
Orthorhombic phase bismuth sulfide (Bi2S3) nanobelts were prepared via  liquid-solid phase reaction method. Bi2S3 nanobelts were observed to be preferentially oriented along the (101) plane. Direct band gap (2.95 eV) and characteristic wavelength (λmax = 342 nm) were extracted through UV-visible spectroscopy. Specific surface area (9.8 m2/g) and pore size (2.5-120 nm) were evaluated through Brunauer-Emmett-Teller (BET) analysis. Relative humidity (RH) sensing properties were studied in the range of 11-97% RH at ambient conditions. The response of the sensor increases linearly with increase in RH. Fast response time (8-10 s) and recovery time (15 s) were observed. Reproducible and large response was also observed between 11 and 97% RH. Small hysteresis (<5%) and long-term stability during 30 days were confirmed. As a function of frequency, capacitance, alternating current conductivity, and electrical complex modulus in the frequency range of 20-2 MHz were studied at 11-97% RH. The sensing mechanism was also studied.